Prosedur Purchase Order pada Departemen General Affairs PT Trakindo Utama Surabaya - Sekar Harum Puspita; Dyah Widowati (Masip: Jurnal Manajemen Administrasi Bisnis dan Publik Terapan, 2025)
The research titled "Purchase Order Procedures at the General Affairs Department of PT Trakindo Utama Surabaya" discusses the purchase order procedures that assist the company’s operations, specifically in the procurement of goods and services within the general affairs department at PT Trakindo Utama Surabaya. The method used is descriptive with a qualitative approach, by describing the results obtained from direct observation and involvement in the company's purchase order activities, along with interviews with experts in the field and supported by various information from literature studies. The research findings show that the purchase order procedures at PT Trakindo Utama Surabaya are structured, repetitive, and have been consistently implemented. These procedures enable efficient management of goods and services procurement, contributing to the smooth operations of the company as a whole. Consistent implementation of these procedures also indicates that PT Trakindo Utama Surabaya has established a stable and reliable procurement system to meet operational needs.